Social Networks in the Vegetable Agribusiness System: The Role of Social Exchange in Shaping Sustainable Partnerships - Safiteri, Puput; Titaley, Elsina; Matakena, Fransina (Baileo: Jurnal Sosial Humaniora, 2023)
This study aims to explore the role of social exchange in shaping sustainable partnerships between vegetable farmers and customers within the agribusiness system in Wayari Hamlet. Using a qualitative approach and in-depth interview methods, this study identifies two main dimensions in the social relations of vegetable agribusiness: the associative dimension, which reflects cooperation, and the dissociative dimension, which reflects the potential for conflict or tension within relationships. The findings show that social exchange, in the form of mutual commitment between farmers and customers, serves as the main foundation for creating mutually beneficial relationships. Farmers provide high-quality and consistent products, while customers offer financial support and long-term loyalty. This relationship not only enhances the economic stability of the farmers but also strengthens social bonds within the community. The novelty of this study lies in its revelation of how social exchange, rather than merely market mechanisms, can serve as an effective strategy to build sustainable agribusiness partnerships. These findings provide significant contributions to the development of social sciences and the humanities, particularly in understanding the dynamics of social relations within community-based local economies. This study recommends the integration of social exchange principles in the design of sustainable agribusiness models and in community-based agricultural development policies.